Pigment epithelium derived factor drives melanocyte proliferation and migration in neurofibromatosis café au lait macules - Charlotte Lovatt; Megan Williams; Alex Gibbs; Abdullahi Mukhtar; Huw J. Morgan; Simone Lanfredini; Carlotta Olivero; Gill Spurlock; Sally Davies; Charlotte Philpott; Hannah Tovell; Peter Turnpenny; et al. (Wiley, 2024)
Abstract Background RASopathies, which include neurofibromatosis type 1 (NF1), are defined by Ras/mitogen‐activated protein kinase (Ras/MAPK) pathway activation. They represent a group of clinically related disorders often characterised by multiple Café au Lait Macules (CALMs). Objectives To determine, using in depth transcriptomic analysis of NF1 melanocytes from CALM and unaffected skin, (1) the gene(s) responsible for melanocyte proliferation and migration, and (2) the activated signalling pathway(s) in NF1 melanoma. Methods Classical NF1 (n = 2, who develop tumours) and 3bp deletion NF1 (p. Met992del, who do not develop tumours) (n = 3) patients underwent skin biopsies from CALM and unaffected skin. Melanocytes were isolated and propagated, with five replicates from each tissue sample. DNA and RNA were extracted for mutational analysis and transcriptomic profiling with six replicates per sample. Mechanistic determination was undertaken using melanocyte and melanoma cell lines. Results All CALMs in NF1 were associated with biallelic NF1 loss, resulting in amplification of Ras/MAPK and Wnt pathway signalling. CALMs were also associated with reduced SERPINF1 gene expression (and pigment epithelium‐derived factor (PEDF) levels, the reciprocal protein), a known downstream target of the master regulator of melanocyte differentiation microphthalmia‐associated transcription factor (MITF), leading to increased melanocyte proliferation, migration and invasion. In classical NF1 and melanoma, but not 3bp deletion NF1, there was also activation of the PI3K/AKT pathway. Pigment epithelium‐derived factor was found to reduce cell proliferation and invasion of NF1 melanoma. Conclusions Melanocyte proliferation and migration leading to CALMs in NF1 arises from biallelic NF1 loss, resulting in RAS/MAPK pathway activation, and reduced expression of the tumour suppressor PEDF. Activation of the PI3K/AKT pathway in classical NF1 and NF1 melanoma may facilitate tumour growth.